Savings, investment and financial development in Fiji : an econometric analysis : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Applied Economics at Massey University, Palmerston North, New Zealand - Edmonds, Fiona (Massey University, 2007)
The vital role of savings, investment and financial sector development in the growth process has been at the heart of economic policy reforms in many developing countries. The key purpose of this study is to examine the determinants of savings (i.e. national and private), investment (i.e. private corporate and non-residential) and the relationship between finance and growth (i.e. causality, stock market development and McKinnon's complementarity hypothesis) for the case of Fiji. This study applies the Auto-regressive Distributed Lag procedure to cointegration and the modified WALD test for non-Granger causality to time series data for various models over the period 1961-2005. The study sets the economic growth literature in the historical perspectives for Fiji and undertakes a comprehensive empirical examination that will enhance the knowledge and future development of economic policies aimed at increasing economic growth. The importance of savings, investment, and the financial sector in contributing to economic growth in developing countries has been clearly highlighted in the literature. Fiji has been chosen as the case study in this analysis due to poor growth performance during the past 20 years. The military coups of 1987 led to political instability and policy failures that had a disastrous impact on the economy through low levels of economic activities. The economic uncertainty experienced by the nation led to various negative effects on capital accumulation, savings, investment and the financial sectors development. This not only diminished business activities, but also affected the household sector in terms of consumption, savings, investment, higher prices and social development. In the wake of the 1987 political and economic crisis, extensive macroeconomic, financial and trade sector reforms were undertaken which represented a revolutionary break from the past policies of import protection, high rates of inflation, agricultural dependence and financial repression. Given the devastating political, economic and social crises, and the poor performance of the economy, this study evaluates the key financial factors to enhance growth. In particular, savings, investment and financial sector development and the policy implications for long term economic growth are investigated. These considerations point to the need for undertaking in-depth investigations to bring together theoretical and empirical analysis in the context of Fiji's economic development. First, the savings-growth performance is examined using an empirical framework based on the lifecycle model. Second, the analysis examines investment and the role of capital formation in growth acceleration in the post independence period based on the theoretical considerations of the neo-classical investment theories. Third, financial sector development and economic growth relationships are examined. In particular, the direction of causality between the financial sector and economic growth, the impact of stock market and financial liberalisation, and the applicability of McKinnon's complementarity hypothesis are investigated for Fiji. The political and economic turmoil that Fiji has experienced suggest various actions required to improve the performance of the economy and also the key economic factors necessary to enhance growth. The findings initiate a number of policy implications that require attention in order to address Fiji's poor economic performance. This is particularly important to reduce the high incidence of poverty which still remains a challenge for policymakers.
Keywords: Fiji Econometric models; Economic development; Financial institutions; Saving and investment; Economic conditions